Elementary School Teachers’ Competence in the Implementation of Learning Evalution - Aqiel Mutawalli; Fachri Husaini Hasibuan; Muhammad Alinafiah; Salman Ahmadi; Haidir Haidir; Mardianto Mardianto (Jurnal Basicedu, 2023)
This study aims to describe the competence of SD/MI level teachers in the learning evaluation process. This is intended as an effort to classify the form of assessment of elementary age children. This study uses a qualitative approach with the method of literature study. Sources of data and study analysis materials are relevant scientific works including books, articles and proceedings. This study concludes that a teacher is required to be able to carry out assessments and evaluations of learning processes and outcomes and to utilize the results of these assessments and evaluations in an effort to take reflective action to improve the quality of learning. Evaluation is interpreted as a systematic process carried out to assess an object based on certain criteria and prerequisites. Some of the evaluation principles needed as a guide in evaluation activities include; valid, objective, fair, integrated, open, comprehensive and continuous, systematic, based on criteria, and accountable. The overall evaluation includes 3 aspects, namely (1) cognitive aspects which are closely related to the ability to think, (2) psychomotor aspects related to physical activity, and (3) affective aspects including character, behavior such as attitudes, interests, self-concept, values and morals.